ACE inhibitor effects of brachial artery structure and function in patients with arterial hypertension - L. V. Melnikova (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To investigate the effects of an angiotensin-converting enzyme (ACE) inhibitor fosinopril on the structural and functional parameters of brachial arteries (BA) in patients with essential arterial hypertension (EAH). Material and methods. The study included 32 EAH patients: 15 men and 17 women aged 27-59 years (mean age 45,6±11,7 years). BA ultrasound and echocardiography (EchoCG) were performed with the use of the Vivid 7 Dimension device (USA). The following parameters of BA remodelling were analysed: intima-media thickness (IMT), lumen diameter (D), and wall-to-lumen (W/L) ratio. BA endotheliumdependent vasodilatation (EDVD) was assessed in the reactive hyperemia test. Central hemodynamic parameters were also assessed. Results. In EAH patients, the six-month fosinopril treatment was associated with BA IMT reduction, but not with substantial intraluminal diameter changes, or increased endothelium-dependent vasodilatation. Conclusion. Among EAH patients, an ACE inhibitor fosinopril demonstrated a marked improvement in BA structural and functional parameters.